2013
DOI: 10.1371/journal.pone.0055420
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dimethylarginine Is Associated with Developmental Programming of Adult Kidney Disease and Hypertension in Offspring of Streptozotocin-Treated Mothers

Abstract: Diabetes mellitus complicates pregnancies, leading to diseases in adult life in the offspring. Asymmetric dimethylarginine (ADMA) is increased in diabetes mellitus, kidney disease, and hypertension. We tested whether maternal diabetes causes increased ADMA in rats, resulting in kidney disease and hypertension in the adult offspring, and whether these can be prevented by maternal citrulline supplementation. Newborn female and pregnant Sprague-Dawley rats were injected with streptozotocin (STZ), which made up th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
158
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(162 citation statements)
references
References 34 publications
3
158
1
Order By: Relevance
“…We also reported that ADMAinduced NO/reactive oxygen species (ROS) imbalance is involved in the development of hypertension in several programming models [6][7][8][9][10]. As shown in Table 2, plasma levels of L-citrulline, L-arginine and ADMA and L-arginine-to-ADMA ratio were not different between control and HF group at both 3 weeks and 3 months of age.…”
Section: Adma and Oxidative Stressmentioning
confidence: 81%
See 1 more Smart Citation
“…We also reported that ADMAinduced NO/reactive oxygen species (ROS) imbalance is involved in the development of hypertension in several programming models [6][7][8][9][10]. As shown in Table 2, plasma levels of L-citrulline, L-arginine and ADMA and L-arginine-to-ADMA ratio were not different between control and HF group at both 3 weeks and 3 months of age.…”
Section: Adma and Oxidative Stressmentioning
confidence: 81%
“…We recently observed that renal programming and hypertension developed in the adult male offspring of mother rats exposed to caloric restriction [6,7], diabetes [8], dexamethasone treatment [9,10] and high-fructose (HF) diet [11]. A number of mechanisms, including glucocorticoid effects, oxidative stress, epigenetic regulation, alterations of renin-angiotensin system (RAS), impaired tubular sodium handling and reduction in nephron numbers, have been put forward to interpret renal programming [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…We found that aliskiren therapy decreased ADMA levels but increased the ratio of l-arginine to ADMA in the plasma, which was consistent with our recent findings showing that ADMA contributed to programmed hypertension and that aliskiren had an ADMA-lowering effect. 5,12 Unlike aliskiren, losartan decreases BP but not ADMA: compared with aliskiren, its BP-lowering effect is similar. However, losartan had no effects on ADMA and NO bioavailability (represented by the ratio of l-arginine to ADMA and NOx) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…5 Kidney homogenate was prepared, and 10 μg of protein was added to 1 mM CPH and 0.1 mM diethylenetriaminepentaacetic acid in a total volume of 100 μl of Chelex-treated PBS. Samples were placed in a 50μl glass capillary (Wilmad Glass, Buena, New Jersey, USA).…”
Section: Detection Of Superoxide By Electron Paramagnetic Resonancementioning
confidence: 99%
See 1 more Smart Citation